VO2MAX, 6-minute walk, and muscle strength each correlate with frailty in US veterans - Seldeen, Kenneth Ladd; Rahman, Ayesha Saqebur; Redae, Yonas; Satchidanand, Nikhil; Mador, M. Jeffery; Ma, Changxing; Soparkar, Mihir; Lima, Alexis Rose; Ezeilo, Ifeoma N.; Troen, Bruce Robert (Frontiers in Physiology, 2024)
Introduction: Frailty often manifests as an increased vulnerability to adverse outcomes, and detecting frailty is useful for informed health care decisions. Veterans are at higher risk for developing frailty and at younger ages. The goal of this study was to investigate approaches in Veterans that can better inform the physiologic underpinnings of frailty, including maximal oxygen uptake (VO2max), 6-minute walk, muscle strength, and inflammatory biomarkers. Methods: Participants (N = 42) were recruited from the Buffalo VA Medical Center. Inclusion criteria: ages 60-85, male or female, any race, and not having significant comorbidities or cognitive impairment. Outcome measures included: the Fried frailty phenotype, the short physical performance battery (SPPB), quality of life (QOL) using the Q-LES-Q-SF, and the following physiologic assessments: VO2max assessment on an upright stationary bicycle, 6-minute walk, and arm and leg strength. Additionally, inflammatory biomarkers (C-reactive protein, IL-6, IL-10, interferon-γ, and TNF-α) were measured using ELLA single and multiplex ELISA. Results: Participants: 70.3 ± 7.4 years of age: 34 males and 8 females, BMI = 30.7 ± 5.4 kg/m2, 26 white and 16 African American. A total of 18 (42.8%) were non-frail, 20 (47.6%) were pre-frail, and 4 (9.5%) were frail. VO2max negatively correlated with Fried frailty scores (r = -0.40, p = 0.03, N = 30), and positively correlated with SPPB scores (r = 0.50, p = 0.005), and QOL (r = 0.40, p = 0.03). The 6-minute walk test also significantly correlated with VO2max (r = 0.57, p = 0.001, N = 42) and SPPB (r = 0.55, p = 0.0006), but did not quite reach a significant association with frailty (r = -0.28, p = 0.07). Arm strength negatively correlated with frailty (r = -0.47, p = 0.02, N = 26), but not other parameters. Inflammatory profiles did not differ between non-frail and pre-frail/frail participants. Conclusion: Objectively measured cardiorespiratory fitness was associated with physical performance, QOL, and frailty in older Veterans. Furthermore, the 6 minute walk test correlated with VO2max and SPPB, but not frailty. Arm strength also correlated with frailty, however the relationship to other indicators of physical performance is unclear.